HRIS GoLive for academic faculty - Mar, Joanne V. (Animo Repository, 2021)
The Culture, Community, and HR Services Office (CCHRSO) announced the rollout of the new DLSU Human Resource Information System, running on cloud-based platforms RAMCO and SUMTOTAL. The streamlining of HR services was made possible through the collaboration of employees who participated in the technical workgroups under the BITUIN (Banner Initiative to Transform, Unify, Integrate, and Navigate) Project. Starting October 1, 2021, the cloud-based system allows the Academic Faculty to access their HR records, HR services, and employee benefits using a digitized and integrated self-service portal to handle and transact requests, including the following: Updating Employee Personal Information including changes in marital status, additional dependents, residential updates, and emergency contact information Uploading of employee credentials such as completion of graduate studies or professional certification acquired during employment Online application for applicable leave types and official business